Inovasi Pendidikan: Dampak Metode Pembelajaran terhadap Peningkatan Literasi Anak Disleksia - Eva Rachel Meisyana Sianipar; Feri Hidayat; Naira Sahda Ranupatma; Shabrina Hafilah; Siti Hamidah (Jurnal Bintang Pendidikan Indonesia, 2024)
Every citizen has the right to education, including children with special needs. One of the activities of education is learning. Learning is a way for a person to develop. By learning someone will have broad insight. But in reality there are some children who have learning difficulties, one of which is dyslexia. Therefore, a method is needed to help the learning process of dyslexic children in reading. The main purpose of this research is to explain some of the development methods that have been done by previous researchers so that they can become recommendations in conducting development methods for children with dyslexia. The results of the review of selected articles state that customizing learning approaches according to the individual needs of the child is very important to ensure the effectiveness of learning. There are three main approaches that can improve dyslexic children's literacy: multisensory approach, auditory approach and visual approach.